Da Spinoza a Gramsci. La formazione filosofica e politica di A. Tosel - Tosel, André (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2018)
In this interview, André Tosel recalls the most important phases of his scientific commitment. He focuses on the different aspects of his theoretical experiences: the left-wing Catholicism, his meeting with Althusser (who shows him the analytical path from Spinoza to Marx), his discovery of Gramsci’s role in the Marxist historicism. Tosel emphasizes the differences between Althusser and Gramsci, recognizing the Italian Marxist – an author not sufficiently studied in France – a point of reference for the elaboration of a critical analysis of the structure of the contemporary capitalism. Of course, according to Tosel, such an appreciation of Gramsci’s work ford not exclude critical evaluations of his contribution. Keywords: Marx, Historical materialism, Spinoza, Althusser, Gramsci, Religion, Hegemony, Languages and practices of the resilience.